Stem Cells From Human Exfoliated Deciduous Teeth-Conditioned Medium (SHED-CM) is a Promising Treatment for Amyotrophic Lateral Sclerosis - Ueda, Tomoyuki; Ito, Taisei; Inden, Masatoshi; Kurita, Hisaka; Yamamoto, Akihito; Hozumi, Isao (Frontiers in Pharmacology, 2022)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder, characterized by the loss of upper and lower motor neurons, for which an effective treatment has yet to be developed. Previous reports have shown that excessive oxidative stress, related to mitochondrial dysfunction and the accumulation of misfolding protein, contributes to ALS pathology. In terms of treatment, it remains necessary to identify effective medicines for multiple therapeutic targets and have additive effects against several disorders. In this study, we investigated stem cells from human exfoliated deciduous teeth (SHED), which release many factors, such as neurotrophic factors and cytokines, and are applied to treat neurological diseases. Specifically, we examined whether SHED-conditioned medium (CM), i.e., the serum-free culture supernatant of SHED, reduced mutant SOD1-induced intracellular aggregates and neurotoxicity. We found that SHED-CM significantly suppressed the mutant SOD1-induced intracellular aggregates and neurotoxicity. The neuroprotective effects of SHED-CM are partly related to heat shock protein and the activation of insulin-like growth factor-1 receptor. SHED-CM also had a protective effect on induced pluripotent stem cell-derived motor neurons. Moreover, SHED-CM was effective against not only familial ALS but also sporadic ALS. Overall, these results suggest that SHED-CM could be a promising treatment for slowing the progression of ALS.